Performance comparison between Islamic and conventional banks using modified TOPSIS with objective weights / Farah Azaliney Mohd Amin ... [et al.] - Mohd Amin, Farah Azaliney; Abdullah, Farah Nazila; Roslan, Siti Nur Aliah; Wan Azman, Wan Nurul Aida (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
The banking system acts as an intermediary between two parties that provides financial services to society, which oversees operating a payment system, taking deposits, providing loans and assisting with investments. Thus, efficiently measuring the performance of the banking sector is vital to beneficiaries who want to assess fiscal conditions and economic health. Hence, this study analysed the financial performance of Islamic and conventional banks in Malaysia. A total of seven Islamic banks and twelve conventional banks that were identified as the principal dealer's banks by the Bank Negara Malaysia (BNM) were observed in this study using the completed and consolidated financial statements of each bank from 2016 to 2020. Since 1979, regulators and policymakers recommended implementing the CAMELS rating system as an effective internal supervisory tool for evaluating and examining banks based on their financial performance (Johnes et al., 2009; Rozzani & Rahman, 2013; Desta, 2016).